The rheology and foamability of crystal-melt suspensions composed of triacylglycerols. Issue 6 (17th January 2022) - Mishra, Kim; Kämpf, Fabian; Ehrengruber, Silas; Merkel, Julia; Kummer, Nico; Pauer, Robin; Fischer, Peter; Windhab, Erich J.
Abstract : The rheology and morphology of triacylglycerol crystal-melt suspensions from anhydrous milk fat, cocoa butter, and palm kernel oil as function of crystallization shear rate and crystal volume fraction is investigated and related to foamability. Abstract : The rheology of triacylglycerol (TAG) crystal-melt suspensions (CMSs) consisting of anhydrous milk fat (AMF), cocoa butter (CB), and palm kernel oil (PKO) as function of crystallization shear rate  cryst and crystal volume fraction Φ SFC is investigated by in-line ultrasound velocity profiling – pressure difference (UVP-PD) rheometry. Measurements up to Φ SFC = 8.8% are presented. Below the percolation threshold Φ c, no yield stress τ 0 is observed and the viscosity η scales linearly with Φ SFC . Above Φ c, a non-linear dependency of both τ 0 and η as function of Φ SFC is apparent. For AMF and CB, the increase in  cryst leads to a decrease in η and τ 0 as function of Φ SFC, whereas for PKO based CMSs the opposite is the case. Scanning electron microscopy (SEM) and polarized light microscopy (PLM) relate these rheological findings to the microstructure of the investigated CMSs by taking the effective aspect ratio a eff and the concept of the effective crystal volume fraction Φ effSFC into account. Foam formation by dynamically enhanced membrane foaming (DEMF) is performed directly after crystallization and reveals that depending on the CMS rheology and crystallite-, crystallite cluster- and crystal floc microstructure, a wide range of gas volume fractions between 0.05–0.6 are achievable.